2004
DOI: 10.6028/nist.sp.800-63v1.0
|View full text |Cite
|
Sign up to set email alerts
|

Electronic authentication guideline

Abstract: This publication has been developed by NIST to further its statutory responsibilities under the Federal Information Security Management Act (FISMA), Public Law (P.L.) 107-347. NIST is responsible for developing information security standards and guidelines, including minimum requirements for federal information systems, but such standards and guidelines shall not apply to national security systems without the express approval of appropriate federal officials exercising policy authority over such systems. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Password strength can be measured by password entropy [16,20]. A mathematical definition of entropy in terms of the probability distribution function is: (1) where, P(X=x) is the probability that the variable X has the value of x.…”
Section: B Password Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Password strength can be measured by password entropy [16,20]. A mathematical definition of entropy in terms of the probability distribution function is: (1) where, P(X=x) is the probability that the variable X has the value of x.…”
Section: B Password Strengthmentioning
confidence: 99%
“…A mathematical definition of entropy in terms of the probability distribution function is: (1) where, P(X=x) is the probability that the variable X has the value of x. The entropy is used to determine the difficulty of the password or key [20]. It can be conventionally expressed in bits.…”
Section: B Password Strengthmentioning
confidence: 99%
“…The password entropy provides a theoretical number representing how unpredictable a password is. The National Institute of Standards and Technology's published guidelines use different variations of entropies to measure password strength (Burr et al, 2004). On the other hand, the password guessability measure indicates the number of guesses required by password-cracking algorithms to guess the given password (Kelley et al, 2012).…”
Section: Password Strengthmentioning
confidence: 99%
“…In recent years, the research focus has shifted from the importance of password policy provision to finding the best password policy to implement in PCSs to ensure that usable and strong passwords are created. Researchers have paid close attention to answering this question because the current guidelines are based on theoretical estimates (Burr, Dodson, & Polk, 2004) and not empirical data. Kelley et al (2012) and Komanduri et al (2011) found that usable and strong passwords are created by enforcing a password policy requiring a minimum of 16 characters without any further restrictions, such as including different character classes.…”
mentioning
confidence: 99%